PERSPEKTIF PEDAGOGIK TENTANG LANDASAN MANAJEMEN PENDIDIKAN - Hasnida, Hasnida; Syofiyanti, Dessy; Khairullah, Khairullah (Universitas Tanjungpura, 2026)
Educational management based on pedagogic principles is the key to creating an effective and quality learning environment. This study aims to examine the application of pedagogic principles in elementary school education management in Riau Province and identify the factors that influence it. The method used was a mixed method with 100 respondents from teachers and principals for quantitative data, and 15 informants for qualitative data through interviews. The results showed that pedagogic principles received high perception from respondents with an average score of 4.03 (Likert scale of 5), and the research instruments showed high reliability (Î± = 0.876). There was also a significant positive correlation between the application of pedagogic principles and the quality of school management (r = 0.614; p < 0.01). Qualitative data reveals that bureaucratic challenges are the main obstacles. The role of the principal as a pedagogic leader is essential in creating a collaborative and innovative climate. Strengthening leadership and simplifying bureaucracy needs to be prioritized so that pedagogic-based management runs effectively.